2022
DOI: 10.1159/000527951
|View full text |Cite
|
Sign up to set email alerts
|

Aptima HR-HPV Testing of Cytology Specimens Is an Effective Supplement for p16 Staining to Improve Diagnostic Accuracy for HPV-Related Oropharyngeal Squamous Cell Carcinoma

Abstract: <b><i>Introduction:</i></b> Regarding a small proportion of oropharyngeal squamous cell carcinoma (OPSCC) patients who tested p16-positive but human papillomavirus (HPV)-negative, we attempted to perform HPV testing to improve the accuracy of HPV detection in OPSCC patients. <b><i>Methods:</i></b> We simultaneously performed Aptima HPV testing of cytological specimens and p16 immunohistochemistry (IHC) staining of histologic biopsies from the same cohort of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…It has the potential to be used for HPV status detection in HNSCC patients since it is a fully automated, affordable and reliable HPV detection platform. However, since this method only works with cytological specimens, in our preliminary study, endoscopic brush cytology was performed at the primary site, and FNA was performed at the metastatic site to obtain feasible specimens for APTIMA HPV detection [29]. In our study, APTIMA HPV testing showed a similarly high sensitivity to p16 IHC in detecting HPV status; however, the speci city analysis yielded a signi cant difference (p = 0.018) favoring APTIMA over p16 IHC.…”
Section: Discussionmentioning
confidence: 60%
“…It has the potential to be used for HPV status detection in HNSCC patients since it is a fully automated, affordable and reliable HPV detection platform. However, since this method only works with cytological specimens, in our preliminary study, endoscopic brush cytology was performed at the primary site, and FNA was performed at the metastatic site to obtain feasible specimens for APTIMA HPV detection [29]. In our study, APTIMA HPV testing showed a similarly high sensitivity to p16 IHC in detecting HPV status; however, the speci city analysis yielded a signi cant difference (p = 0.018) favoring APTIMA over p16 IHC.…”
Section: Discussionmentioning
confidence: 60%
“…In such instances, FNAC may constitute the sole available specimen for the initial diagnosis and molecular characterization. Various methodologies validated on cervicovaginal cytological specimens have undergone assessment on HN FNAC, forming an integral part of routine practice for confirming OPSCC or the diagnosis of HN‐CUP 6,10,19–22 …”
Section: Discussionmentioning
confidence: 99%
“…In this clinical context, the significance of HPV status on FNAC samples can guide the diagnostic workup and therapeutic management, indicating an oropharyngeal origin. Furthermore, reliable HPV testing techniques on cytological samples become imperative 10–12 …”
Section: Introductionmentioning
confidence: 99%
“…From a practical standpoint, mRNA testing is not done in practice because the results from p16 immunohistochemistry and in situ hybridization for HPV are generally considered reliable enough for clinical decision-making. It must be recognized, however, that concordance rates between tests can still be variable (17)(18)(19)(20)(21).…”
Section: Clinical Datamentioning
confidence: 99%